Indirectly heated carbonate looping cycles in cement plants for CO2 capture and storage - Rezvani, Sina; Rolfe, Angela; Franco, Flavio; Brandoni, Caterina; Böge, Kyra; Hewitt, Neil; Huang, Ye (Applied Thermal Engineering, 2025)
The concept of Carbonate Looping Cycle (CaL) offers many advantages compared to other CO2 capture technologies within cement plants. The configurations currently discussed in the literature employ oxy-fuel combustion to supply the necessary heat for the calcination process in a single reactor. As a result, the process requires an air separation unit. The indirectly heated calcium looping (IHCaL) offers solutions to overcome the present limitations. Numerous heat pipes connecting a separate combustion unit to a calciner supply thermal energy for the calcination process. This study, based on the best available technology, recommends both full and tail-end IHCaL integrations within a commercial cement plant. Both systems provide over 1.3 million tonnes of cement per annum. The fully integrated option produces 309 GWh of electricity, compared to 875 GWh for the tail-end option. The CO2 avoidance rates for fully integrated and tail-end options are 0.83 and 0.88 t CO2/t Clinker, respectively. The tail-end version has a notably high capital cost, resulting in a high CO2 avoidance cost of €37.6/t CO2. On the other hand, the fully integrated version lowers the CO2 avoidance cost to €29.8/t CO2 because of a lower capital requirement and a smaller gap between the amount of CO2 captured and avoided.
CRIS-Team Scopus Importer:2025-01-31
Keywords: Calcium looping cycles; Decarbonising cement plants; Heat pipes; Indirectly heated calcination; Post-combustion capture; Techno-economic analysis